Depiction of Adolescents Smoking Behaviour in Urban and Suburban - Toghur Arifani Lubis; R. Kintoko Rochadi (Britain International for Academic Research (BIAR) Publisher, 2020)
Smoking is a fatal issue that has not yet been resolved and spread even among adolescents particularly in Indonesia. This study aim to depict the adolescents smoking behavior in SMPN three Medan or urban areas and MTS Amin Darussalam Deli Serdang or suburban areas. This cross sectional study conducted on October. Data were collected using questionnaires toward students from both school. Results shows majority respondent in urban have good knowledge, negative attitude toward cigarette and non-smokers but interested in smoking, majority of former smokers in urban firstly tried smoking during sixth grade elementary because of peer influence, smoking occasionally, ever smoked one to five cigarettes per day, quit smoking because of self-awareness and still have interest in smoking. Furthermore, majority respondent in suburban have bad bad knowledge, negative attitude toward cigarette, smoker, firstly tried smoking during sixth grade elementry because of peer influence, smoking occasionally, ever smoked one to five cigarettes per day and have no intention to quit smoking, majority of former smokers quit smoking because of caught by parent or teacher and still have interest in smoking. In conclusion, there is difference of smoking behavior between urban and suburban, the depiction of smoking behavior in suburban is worse than in urban because it has higher number of smokers, poorly dominant of knowledge and have no intention to quit smoking.